AN EMPIRICAL INVESTIGATION OF THE RELATIONSHIP BETWEEN RETAIL STORE ATTRIBUTES AND CUSTOMER SATISFACTION (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
It is the goal of this study to examine the  relationship between consumer satisfaction  and various retail business attributes. As  everyone know that Indian retail industries are  flourishing and Organised retail is chipping  away at brick-and-mortar businesses’ market  share. According to the findings of previous  research, the scale used to assess customer  satisfaction includes store atmosphere, shopping  convenience, operational competence, service  quality, product selection, pricing policy, and  services given after the sale. Using a sample  of 274 Big Bazaar consumers in West Bengal,  India, we tested the suggested model using  Smart PLS. According to this study, customers’  satisfaction in the retail business is influenced by  a variety of shop factors. Store attributes were  shown to be the most significant antecedent  of customer satisfaction. By analysing the  dimensions of perceived customer satisfaction,  this research adds to the understanding the  concepts of customer satisfaction. In this study,  further research should be done to analyse  consumer satisfaction in a variety of retail  sectors. A comparison of this idea with other  retail categories will be possible. Furthermore,  Interrelationship between customer satisfaction  components in the retail business must also be  studied in details. According to this study, retail managers  and executives should aim to influence the  atmosphere of their shops as well as the ease  of shopping as well as the service quality,  product selection, pricing strategy, and after sale services.
Keywords: Retail Store attributes; Service Quality; Store atmospherics; Customer Satisfaction